WHO MAKES ADOLESCENTS HAPPY? AN EXPLORATIVE STUDY USING THE INDIGENOUS PSYCHOLOGY APPROACH - Annisa Soleha Hamka; Kwartarini Wahyu Yuniarti; Moordiningsih moordiningsih; Uichol Kim (Universitas Muhammadiyah Surakarta, 2015)
This study is aimed at discovering who the source of happiness is for adolescents and how he or she accomplishes his or her role in creating happiness. A number of 458 senior high school students completed an open-ended questionnaire developed by Kim and Park (2008). An indigenous approach is used to analyse respondents’ answers to the open-ended questionnaire. A categorization of respondents’ answers and cross tabulation is also conducted. Analysis results show that a majority of adolescences’ source of happiness derives from the family (50.1%), and friends (27%). Their role in creating happiness was by supporting (54.3). Acceptance of adolescents (20.8%) was also a source of happiness for adolescents. Providing facilities and prayers was also a role given for adolescents.